Plant Ecology Traditional Approaches to Recent Trends - Yousaf, Zubaida (IntechOpen, 2017)
This book is aimed to cover the phylogenetic and functional ecology with special reference to ecological shifts. I hope this book may benefit the students, fellow professors, and resource managers studying plant sciences. Since the topics stated in this book are not new but the issues and technologies mentioned were new to me, I expect that they will be new and equally advanced for the readers too. I encourage the readers to get out into the field to identify plants and to dig out the anthropogenic and social activities effecting plants to come along with the development of plant ecology; to rise and serve the topic of the enormous number of plants facing extinction; and to relish themselves and make some effort to contribute something to the world.